Meningococcal infection in children: factors influencing outcome - O. V. Samodova; E. A. Krieger; L. V. Titova; O. Yu. Leonteva (Журнал инфектологии)
Generalized forms of meningococcal infection are characterized by high risk of complication and fatal outcomes. In Russian Federation, 2016, meningococcal infection was the second most common cause of pediatric deaths (25%) due to infectious diseases after community associated-pneumonia. Mandatory vaccination against meninococcal infection is not regulated, and immunization coverage according to epidemic indications is insufficient. During first 6–8 hours of illness clinical signs of this infection may be non-specific, because of that it is difficult to make correct diagnosis at outpatient department. Aim of the study was to analyze mistakes of diagnostics of meningococcal infection and to assess factors influencing the disease outcome. Material and methods. Retrospective cohort study was performed including 113 pediatric cases of generalized meningococcal infection occurred in Arkhangelsk region (46 cases with fatal outcome and 67 patients, who recovered). Factors influencing the outcome were recognized using Cox regression. Results. Median age of patients was 11 months. Clinical forms were meningitis (13,3%), meningococcemia (40,7%), mixed form (46%). The diagnosis of meningococcal infection was made at outpatient department in 36,9% of cases. The main causes of diagnostic mistakes were the lack of experience among primary care physicians and non-specificic symptoms during the first hours of the disease. Age younger 2 years, septic shock and time between onset of the diseases and admission to the hospital were associated with fatal outcome. Conclusion. To manage meningococcal disease we need to have good compliance with clinical guidelines for outpatient departments and hospitals; to optimize medical students education for prevention of diagnostic mistakes. Vaccination is the most effective method of prevention of deaths associated with meningococcal infection.